Coping among people living with HIV/AIDS (PLWHA). influence of social support, self-esteem, health locus of control and gender (2005)
This study investigated the influence of social support, self-esteem, locus of control and gender on coping behaviour of People Living With HIV/AIDS (PLWHA). One hundred and three (103) PLWHA; 56 males and 47 females with mean age of 29.52 selected using the purposive sampling technique participated in the study. Data were collected with a structured questionnaire and an ex-post tecta-reseerch design was employed. Result of analysis using a multiple regression indicated that social support, self-esteem, health locus of control and gender have significant joint influence with coping (F (4, 73) =5.59, p<.05). The t-test analysis showed that there is no gender difference in coping behaviour of PLWHA (t (101) =;-.60,p>.05). It is then concluded that management of HIV/AIDS should take a multidisciplinary approach, social support should be in the front burner, society should be sensitized to the importance of social support that is culturally appropriate and behaviour modification focused.